Perbandingan Performa Kecepatan dari Algoritma Hash Function untuk Proses Enkripsi Password - Ahmad Miftah Fajrin (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Hash Function is a crucial component in the field of cryptography. It is also utilized for authentication processes within a system. Authentication processes need to ensure both security and data processing speed. One vital component in the authentication process is the password. Password security can be enhanced through encryption using hash functions. Algorithms that can be employed include SHA-1 until SHA-3, MD5 and BLAKE2. Performance testing for execution speed and password comparison is conducted on these algorithms. The results indicate that the BLAKE2 algorithm has an average encryption time of 0.9857. Likewise, for the password comparison process, the BLAKE2 algorithm also exhibits a high speed with an average of 0.2230. As a result, the BLAKE2 algorithm is recommended for use in system authentication.